2018
DOI: 10.1111/echo.14197
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of carotid arteries: Current concepts, methodologies, diagnostic criteria, and technological advancements

Abstract: Following cardiac disease and cancer, stroke continues to be the third leading cause of death and disability due to chronic disease in the developed world. Appropriate screening tools are integral to early detection and prevention of major cardiovascular events. In a carotid artery, the presence of increased intima‐media thickness, plaque, or stenosis is associated with increased risk of a transient ischemic attack or a stroke. Carotid artery ultrasound remains a long‐standing and reliable tool in the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 79 publications
(168 reference statements)
1
31
1
Order By: Relevance
“…CIMT is defined as the distance between the lumen–intima and the media–adventitial interfaces of a segment of the carotid artery and can reflect progression of atherosclerosis or non-atherosclerotic enlargement of the arterial wall. Variability in the measurement of CIMT makes it difficult to compare between studies or combine results from different studies [ 31 ]. Despite these limitations, many studies have demonstrated that CIMT is associated with the presence and severity of atherosclerosis and predicts cardiovascular events, as reviewed by Katakami et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CIMT is defined as the distance between the lumen–intima and the media–adventitial interfaces of a segment of the carotid artery and can reflect progression of atherosclerosis or non-atherosclerotic enlargement of the arterial wall. Variability in the measurement of CIMT makes it difficult to compare between studies or combine results from different studies [ 31 ]. Despite these limitations, many studies have demonstrated that CIMT is associated with the presence and severity of atherosclerosis and predicts cardiovascular events, as reviewed by Katakami et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the above mentioned data, the association of subclinical hypothyroidism and atherosclerosis is still debated, although hyperlipidemia is usually present (79, 95). Carotid artery intima-media thickness measurement remains a long-standing and reliable diagnostic modality used to assess vascular morbidity at an early stage (96). A recent study revealed that carotid artery intima-media thickness is significantly higher in patients with both overt and subclinical hypothyroidism compared with normal control subjects (97).…”
Section: Atherosclerosis and Hypothyroidismmentioning
confidence: 99%
“…CP, which can also be effectively detected by vascular ultrasound, is a manifestation of atherosclerosis and appears to be a stronger cardiovascular risk predictor in comparison to IMT measurements alone. 12,13 MetS is regarded as a marker of higher cardiovascular risk. However, the relationship between carotid artery changes, which can be evaluated by distinct ultrasound parameters, and OAB symptoms in women with MeTS has not been properly investigated so far.…”
Section: Introductionmentioning
confidence: 99%